Development of psoriasis in a patient with chronic myelogenous leukaemia during nilotinib treatment. (28th June 2013) - Nagai, Tadashi; Karakawa, Masaru; Komine, Mayumi; Muroi, Kazuo; Ohtsuki, Mamitaro; Ozawa, Keiya
Abstract The tyrosine kinase inhibitor (TKI) imatinib has been shown to promote psoriasis in some patients with chronic myelogenous leukaemia (CML), but it remained unclear whether second‐generation TKIs such as nilotinib and dasatinib had a similar potential. Here, we present a patient in whom psoriatic erythema appeared at 26 months after initiation of nilotinib treatment. Topical ointments of activated vitamin D3 derivative and corticosteroid were applied; whereupon, the erythema gradually improved. During the clinical course, nilotinib administration continued without reduction in its dose. This is the first report of psoriasis that developed during nilotinib treatment. We also discuss the mechanisms of nilotinib‐mediated progression of psoriasis.